The role of media professionals in perpetuating and disrupting stereotypes of women in Science, Technology, Engineering and Math (STEM) fields - Corsbie-Massay, Charisse L'Pree; Wheatly, Michele G. (Frontiers in Communication, 2022)
Women continue to be underrepresented in the Science, Technology, Engineering and Mathematics (STEM) fields despite efforts to enhance interest and persistence at all levels in the educational pipeline. The “chilly” climate documented for girls and women in STEM exists within a broader communication climate established and reinforced by media professionals. The present study examined the role of media professionals in perpetuating stereotypes of women in STEM through two approaches (1) conducting interviews with seventeen STEM women about their engagement with media professionals and (2) surveying 105 media professionals about their stereotypes about science and scientists. STEM women report positive interactions with the media despite incidents of unprofessionalism, dissonance between the processes and pace of science vs the media, an undercurrent of issues pertaining to gender and other forms of representation, and an ethical responsibility to engage with media. The survey of media professionals revealed persistent stereotypes about scientists across both genders, and these stereotypes were more pronounced among those who engaged with science as part of their job, particularly among those working in entertainment and advertising and those working outside of journalism and social media. To establish greater equity in STEM fields and the knowledge pipeline, communication scholars must investigate the role of media professionals in this process and consider best practices to disrupt media stereotypes about STEM women.